Life in Translation - Reisenberger, Azila Talit (Book collections on Project MUSE., 2008)
Azila Talit Reisenberger is a Bible scholar, a rabbi, a mother, a wife and a poet. In all these selves she grapples with translating her life from Hebrew to English and back again. Life in Translation is full of wry humour, longing, bitterness, sweetness, playfulness and subversions of traditional meanings and texts--a delightful book that charms and surprises anew with each reading.